Developing a COVID-19 WHO Clinical Progression Scale inpatient database from electronic health record data. (15th March 2022) - Ramaswamy, Priya; Gong, Jen J; Saleh, Sameh N; McDonald, Samuel A; Blumberg, Seth; Medford, Richard J; Liu, Xinran
Abstract: Objective: There is a need for a systematic method to implement the World Health Organization's Clinical Progression Scale (WHO-CPS), an ordinal clinical severity score for coronavirus disease 2019 patients, to electronic health record (EHR) data. We discuss our process of developing guiding principles mapping EHR data to WHO-CPS scores across multiple institutions. Materials and Methods: Using WHO-CPS as a guideline, we developed the technical blueprint to map EHR data to ordinal clinical severity scores. We applied our approach to data from 2 medical centers. Results: Our method was able to classify clinical severity for 100% of patient days for 2756 patient encounters across 2 institutions. Discussion: Implementing new clinical scales can be challenging; strong understanding of health system data architecture was integral to meet the clinical intentions of the WHO-CPS. Conclusion: We describe a detailed blueprint for how to apply the WHO-CPS scale to patient data from the EHR.